Pemberdayaan Guru Yayasan Pendidikan Al Khairaat Yogyakarta pada Penanggulangan Antimicrobial Resistance: dari UNAIR untuk Indonesia - Wahyunitisari, Manik Retno; Koendhori, Eko Budi; Endraswari, Pepy Dwi; Purwono, Priyo Budi; Juniastuti, Juniastuti; Wiqoyah, Nurul; Sardjono, Lindawati Alim; Vermasari, Naritha; Muna, Nafdzu Makhmudatul; Setiawan, Firman; Lindarto, Wira Widjaya; Widyatama, Fikri Sasongko (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Antibiotics are compounds created by microorganisms to live by destroying their competitors. Antibiotics are commonly used without a prescription to treat symptoms caused by non-bacterial infections. Antibiotic resistance is a global problem. Continuous education is needed by agents of change to overcome this problem. Community service collaboration between the Department of Microbiology-Parasitology, FK Unair, and the Department of Microbiology, Faculty of Medicine, Public Health, and Nursing, Gadjah Mada University with partnerships for the goals teachers from the Al Khairaat Yogyakarta educational foundation, aim to provide an understanding of the proper use of antibiotics. The initial target of transfer of knowledge was successfully measured by increasing participants' post-test results.